THE ROLE AND IMPORTANCE OF CHEMISTRY IN HIGHER MILITARY EDUCATION - S.Y.Botirova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
the article covers the teaching of chemistry FA in higher military education, the importance of inorganic, organic, analytical, physical and colloidal chemistry in the military field.